Mechanical confinement triggers glioma linear migration dependent on formin FHOD3 - Monzo, Pascale; Chong, Yuk Kien; Guetta-Terrier, Charlotte; Krishnasamy, Anitha; Sathe, Sharvari R.; Yim, Evelyn K.F.; Ng, Wai Hoe; Ang, Beng Ti; Tang, Carol; Ladoux, Benoît; Gauthier, Nils C.; Sheetz, Michael P. (Molecular Biology of the Cell, 2016)
Glioblastomas are extremely aggressive brain tumors with highly invasive properties. Brain linear tracks such as blood vessel walls constitute their main invasive routes. Here we analyze rat C6 and patient-derived glioma cell motility in vitro using micropatterned linear tracks to mimic blood vessels. On laminin-coated tracks (3-10 ìm), these cells used an effi-cient saltatory mode of migration similar to their in vivo migration. This saltatory migration was also observed on larger tracks (50-400 ìm in width) at high cell densities. In these cases, the mechanical constraints imposed by neighboring cells triggered this efficient mode of migration, resulting in the formation of remarkable antiparallel streams of cells along the tracks. This motility involved microtubule-dependent polarization, contractile actin bundles and dynamic paxillin-containing adhesions in the leading process and in the tail. Glioma linear migration was dramatically reduced by inhibiting formins but, surprisingly, accelerated by inhibiting Arp2/3. Protein expression and phenotypic analysis indicated that the formin FHOD3 played a role in this motility but not mDia1 or mDia2. We propose that glioma migration under confinement on laminin relies on formins, including FHOD3, but not Arp2/3 and that the low level of adhesion allows rapid antiparallel migration.
CRIS-Team Scopus Importer:2024-02-19